Identificação de isoformas de Blomia tropicalis (Acari: Echimyopodidae) ligantes de anticorpos IgE de pacientes sensibilizados a ácaros da poeira domiciliar - Almeida, Karine Cristine de (2010)
Background: Blomia tropicalis (Bt) is a common house dust mite in tropical regions and important source of allergens for the induction of respiratory allergic diseases. Most Bt allergens identified so far, however, have shown sequence homology to other dust mite allergens, such as Dermatophagoides spp. The aim of this study was to investigate major IgE-binding isoforms for screening Bt allergens. Methods: We used two-dimensional (2D)-gel electrophoresis of crude Bt extract and sera from mite-sensitized patients with positive skin prick test to Bt that were screened for specific IgE antibodies in ELISA, followed by one-dimensional (1D-) and 2D-immunoblots. Inhibition 1D-immunoblot was performed to visualize the crossreactivity with Dermatophagoides spp. From 2D gels, corresponding IgE-binding spots were excised and identified by mass spectrometry. Results: IgE-binding Bt allergens with low molecular weight (LMW, 14-16 and 25 kDa) and high molecular weight (HMW, 54-134 kDa) showed >50% recognition and were considered immunodominant bands. A high homologous inhibition rate (>80%) was demonstrated with all immunodominant bands. Nearly all HMW immunodominant components showed an expressive rate of heterologous inhibition. However, the low heterologous inhibition was found to LMW immunodominant compounds (25 and 14 kDa). More than 50 spots were identified by stained 2D gel of Bt extract, from which 15 allergens showed IgE reactivity in 2D-immunoblot. Blo t 3 isoforms with enzymatic molecular function of trypsin were identified by mass spectrometry. Blo t 11 was considered as a hypothetical allergen. Other IgE-binding isoforms, such as the enzymes aldehyde dehydrogenase (Blo t ALDH), hexosaminidase (Blo t HEXM), and unknown function (Blo t 2) were also identified. Conclusions: The results indicate several isoforms (Blo t 11, Blo t 3, Blo t 2 and probably Blo t ALDH and Blo t HEXM ) from B. tropicalis recognized by IgE antibodies in Brazilian mite-allergic patients as potential candidates for diagnosis and allergen-specific immunotherapy of allergic diseases.